Selection of Literary Texts for Reading in Foreign Audience. - Швец, А. Д. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
Different views concerning the principles for the selection of literary texts (LT) for reading in foreign audience have been analyzed in the article. Motives and purposes of teaching modern foreign students-translators reading skills have been considered. Criteria for the selection of LT in foreign-language audience have been formulated